Doctoring the South : southern physicians and everyday medicine in the mid-nineteenth century - Stowe, Steven M., 1946- (Studies in social medicine., 2004)
Steven M. Stowe provides an in-depth study of the midcentury culture of everyday medicine in the South. Reading the personal letters, day-books, diaries, bedside notes, and published writings of doctors, Stowe illuminates a world of sickness and remedy, suffering and hope, and the ties between medicine and regional culture.